An Analysis of Yield Curve Notes - OGDEN, JOSEPH P. (Journal of Finance, 1987)
ABSTRACT This paper analyzes a new type of security, the yield curve note, which pays interest at a rate that varies inversely with short‐term interest rates. A valuation model for yield curve notes is presented, the parameters of the model are estimated empirically, and the estimated model is used to explore, in simulation, the price behavior and risk characteristics of yield curve notes in comparison with fixed‐rate notes. The risk of a yield curve note is approximately twice as great as a fixed‐rate note with the same maturity. The unique risk characteristics of yield curve notes make them useful (as liabilities) in immunization strategies for financial institutions. Their usefulness in this regard may be the chief rationale for their development.